Кроскультурна комунікація як важливий чинник підготовки сучасного фахівця - Чередник, Людмила (Видавництво Львівської політехніки, 2020)
The theses are devoted to the problems of developing the skills of cross-cultural communication in the process of training modern specialists in various fields. Cross-cultural communication is based on the characteristics of culture, behavior, mentality of different peoples.
Keywords: cross-cultural communication; business; culture; professional competencies